Minimum connecter of pipelines from Tema/Takoradi to all the regional capitals of Ghana - Galley, John Torgbui (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Science in Industrial Mathematics